EFFECT OF STARVATION ON THERMOELASTOHYDRODYNAMIC LUBRICATION OF ROLLING / SLIDING CONTACT - Basim A. Abbas; Somer M. Nacy (Journal of Engineering, 2006)
A complete numerical solution of thermal compressible elastohydrodynamic lubrication of rolling / sliding contact was achieved to determine the effect of inlet boundary condition on the film shape, film pressure, and film temperature in an elastohydrodynamic line contact problem. The direct iterative technique is used to solve the simultaneous system of Reynolds, ,elasticity , and energy equations for different locations of inlet oil fed . The effect of various load, speed , and slip conditions have been investigated . the results indicate that the effects of starvation are an increase of oil film temperature and decrease in oil film thickness so that the temperature effect are significant and can not be neglected.